High-risk HPV distribution and importance of continuing cervical cancer screening of women aged 65 years and older: a study based on 2 152 766 women in China - Bo Wu; Yu Jiang; Jiahui Wang; Xiaotian Li; He Wang; Fanghui Zhao; Zichen Ye; Yingyu Zhong; Shuyan Jin; Xuelian Zhao; Yueyun Wang (Gynecology and Obstetrics Clinical Medicine)
Objective Current guidelines recommend discontinuing screening for women≥65 years with a history of normal primary cervical cancer screening results. However, the necessity of continued screening in this population remains debated. This study aims to evaluate the importance of cervical cancer screening in women aged≥65.Methods This retrospective study analysed cervical cancer screening data from Shenzhen (2017–2023) to assess the distribution of high-risk human papillomavirus (hr-HPV), the prevalence of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) and the association between hr-HPV and CIN2+ risk in women aged≥65 and <65, comparing the two age groups.Results A total of 2 152 766 records were analysed, including 17 420 women aged≥65 (0.81%). The hr-HPV prevalence in women aged≥65 was 13.67%, with a CIN2+ detection rate of 3.33‰ and a cancer rate of 0.92‰, compared with 8.08%, 1.55‰ and 0.1‰, respectively, in women aged<65 (all p<0.001). Single, double and triple hr-HPV infections were found in 10.56% (n=1839), 2.32% (n=404) and 0.57% (n=99) of cases in women aged≥65, with CIN2+ detection rates of 2.01%, 2.73% and 4.04%, respectively, all exceeding those aged<65 (all p<0.001). The most common genotypes in older women were HPV52, HPV16, HPV58, HPV56 and HPV68, with HPV18, HPV16 and HPV33 being major causes of CIN2+, along with frequent double infections such as HPV52/58, HPV16/52 and HPV52/56, while CIN2+ was predominantly associated with HPV33/39, HPV35/31 and HPV18/39, which differ from those in younger women. A dose-response relationship between hr-HPV infections and CIN2+ risk was observed in women aged≥65 (p for trend<0.001). ORs for CIN2+ were 55.86 (95% CI 21.81 to 143.07), 65.95 (95% CI 22.63 to 192.18) and 85.45 (95% CI 24.15 to 302.35) for single, double and triple or more hr-HPV infections, respectively, but the ORs were lower in women aged<65.Conclusions Women aged≥65 bear a higher cervical cancer burden than those<65. Moreover, hr-HPV infections and their pathogenicity exhibit unique patterns in this older group. Therefore, targeted screening and intervention are essential for women aged≥65. Tailored strategies should be implemented based on national contexts.